Secondary science teachers investigative skills, teacher training and curriculum development - Fernando, Maria Alma Magnayon (2005)
This study tried to establish the influence of selected teacher factors and selected school factors and sources of information on science teachers' investigative skills and teaching competence. The study employed the survey method, which used six instruments to gather the data: the teachers' background information, attitude and interest scale, laboratory skills test, inquiry skills test, teaching competency checklist and classroom observation guide. 51 high school science teachers from public schools served as the sample of the study. It was found that a science teacher's academic preparation and number of years as a science teacher are considered to be the most important factors necessary for attaining good investigative skills while his attitude toward handling science subjects is the most significant teacher factor that influences competence.
"October 2005."
Thesis (Ph.D. Biology Education)--University of the Philippines, Diliman.
Keywords: Science teachers -- Training of -- Philippines; High school teachers -- Training of -- Philippines; High school teachers -- Ability testing -- Philippines; Science teachers -- Employement -- Philippines